Revisions and dissents : essays - Gottfried, Paul (Dekalb [Illinois] : Northern Illinois University Press, 2017)
Paul Gottfried's critical engagement with political correctness is well known. The essays in Revisions and Dissents focus on a range of topics in European intellectual and political history, social theory, and the history of modern political movements. With subjects as varied as Robert Nisbet, Whig history, the European Union election of 2014, and Donald Trump, the essays are tied together by their strenuous confrontation with historians and journalists whose claims about the past no longer receive critical scrutiny. According to Gottfried, successful writers on historical topics take advantage of political orthodoxy and/or widespread ignorance to present questionable platitudes as self-evident historical judgments. New research ceases to be of importance in determining accepted interpretations. What remains decisive, Gottfried maintains, is whether the favored view fits the political and emotional needs of what he calls "verbalizing elites." In this highly politicized age, Gottfried argues, it is necessary to re-examine these prevalent interpretations of the past. He does so in this engaging volume, which will appeal to general readers interested in political and intellectual history.
Reminiscences -- Robert Nisbet : conservative sociologist -- Defining right and left -- The problem of historical connections -- Liberal democracy as a God term -- Origins of the state -- Reexamining the conservative legacy -- Whig history revisited -- The European Union election, 2014 -- The English Constitution reconsidered -- Redefining classes -- Did Mussolini have a Pope? -- Heidegger and Strauss : a comparative study -- Explaining Trump.
Includes index.
Print version record.
JSTOR
Keywords: Conservatism; Liberalism; Right and left (Political science); Political science -- Philosophy; Free enterprise; Conservatisme; Libéralisme.; conservatism; liberalism; Free enterprise; Conservatism; Liberalism; Political science -- Philosophy; Right and left (Political science)